Teachers' Strategies for Building Children's Attitude of Tolerance in Inclusive Schools - Hayati, Miratul; Zahra, Salsa Luthfiyah (Journal of Early Childhood Education (JECE), 2024)
Inclusive schools are heterogeneous educational institutions in which regular children and children with special needs work together in teaching and learning activities. Therefore, an attitude of tolerance is the main basis for establishing harmonious relationships between children in school. This research examines teachers' strategies for forming children's tolerant attitudes in inclusive schools. This research uses a descriptive qualitative approach with data collection techniques using 3 methods, namely observation, interviews, and documentation. The research subjects were teachers and children aged 4-6 years in inclusive schools. The data analysis techniques use the Miles and Huberman model, namely data reduction, data presentation, and conclusion. The results of the research show that there are 3 teacher strategies in building an attitude of tolerance in inclusive schools, namely: adding aspects of tolerance to teaching and learning activities, paying attention to and designing environmental conditions that are effective and efficient, and using flexible learning models.